Infectious Bovine Rhinotracheitis (Ibr) on Cattle in Indonesia and The Strategy For Disease Control - R.M. Abdul Adjid; M Saepulloh (Indonesian Center for Animal Research and Development, 2010)
Infectious Bovine Rhinotracheitis (IBR) caused by Bovine herpesvirus-1 (BHV-1) infects cattle and widely spreads in Indonesia. The disease infected cattle in breeding centers, artificial insemination centers and also holderfarmers. This infectious disease may cause economical losses primarily due to reproductive failure of infected animals. Recommended strategy for disease control is step by step control with priorities, started from upper to downstream, from breeding and artificial insemination (AI) centers as the first priority, then village breeding centers as the second priority, and the last priority is in cattle owned by smallholders. In the breeding and AI centers, eradication of the disease is carried out by surveilance, excluding reactors, and applying biosecurity. In the village breeding centers, the use of semen for AI should come from centers that free from IBR, the use of bull that free from IBR, surveilance and application of biosecurity. At the farmer levels, IBR control is bone by using semen from AI centers free from IBR and routine vaccination. The final step is performed after evaluating the successful rate and economic impact of the disease control. Key words: Cattle, IBR